Explaining Happiness Trends in Europe - Richard A. Easterlin; Kelsey J. O'Connor (Institute of Labor Economics (IZA), 2023)
In Europe differences among countries in the overall change in happiness since the early 1980s have been due chiefly to the generosity of welfare state programs— increasing happiness going with increasing generosity and declining happiness with declining generosity. This is the principal conclusion from a time series study of ten Northern, Western, and Southern European countries with the requisite data. In the present study cross-section analysis of recent data gives a misleading impression that economic growth, social capital, and / or quality of the environment are driving happiness trends, but in the long-term time-series data these variables have no relation to happiness. Significance: Over the past five decades happiness has emerged as a subject of social science research and a potential goal of public policy. But how can a country's happiness be increased? On this, there is a conflict between a number of policy alternatives – promote economic growth, increase social capital, improve the environment, expand welfare state programs. Each of these has point-of-time (cross-section) evidence supporting its claim, but there are very few long-term time-series studies. This article presents newly available time-series evidence that supports the importance of welfare state policies.
Keywords: I31; I38; D60; O10; Q53; Z13; 330; economic growth; happiness; life satisfaction; subjective well-being; long-term; welfare programs; social capital; trust; quality of environment; cross section; time series; Europe; Easterlin Paradox